Pengembangan Media Pembelajaran Ular Tangga Berdiferensiasi pada Mata Pelajaran Fikih di MTsN 6 Agam - Rani Anggraini; Siska Yulia Rahmi (ANWARUL, 2026)
Low student engagement in Fiqh learning is associated with the predominance of conventional methods that have not accommodated diverse learning styles. This condition indicates the need for learning media that align with students’ characteristics through a differentiated approach. This study aimed to develop a differentiated snakes-and-ladders learning medium that is feasible and practical for use in Fiqh learning. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the analysis, design, development, implementation, and evaluation stages. The research participants consisted of 31 Grade VII.8 students at MTsN 6 Agam. Data were collected through observations, interviews, questionnaires, and documentation and subsequently analyzed using quantitative descriptive techniques. The results showed that the developed medium achieved a feasibility score of 93.19%, placing it in the highly feasible category. The practicality test results showed a teacher response rate of 100% and a student response rate of 85%, both of which fell within the highly practical category. The use of this medium also indicated increased student engagement and learning motivation. Thus, the differentiated snakes-and-ladders learning medium was considered feasible and practical for supporting Fiqh learning. This medium provides an interactive learning alternative that accommodates student diversity and is relevant for implementation in schools with limited access to technology.